From Smileys to Smileycoins: Using a Cryptocurrency in Education - Gunnar Stefansson; Jamie Lentin (Ledger, 2017)
This paper describes a cryptocurrency to reward students for their studies. The currency bears the apt name Smileycoin or SMLY and is used within the tutor-web online learning platform. In order to make the SMLY attractive to students several approaches have been used, including support from companies whose services can be purchased for SMLY. The paper describes the use of the SMLY as a reward mechanism in a large undergraduate calculus course, including student adoption, student use of SMLY, coinbase use for education in low-income areas, and response to abuse.